2019
DOI: 10.1002/vms3.168
|View full text |Cite
|
Sign up to set email alerts
|

Risk mapping and eco‐anthropogenic assessment of anthrax in the upper Zambezi basin

Abstract: In Zambia, anthrax has emerged as a serious disease decimating humans, livestock and wildlife with devastating effects on eco‐tourism resulting in the destabilization of major pristine wildlife sanctuaries. Consequently, the thrust of this study was to establish the spatial distribution of anthrax and determine ecological drivers of its recurrence, maintenance and epidemiological linkage to anthropogenic activities. Environmental and biological samples were collected within the livestock production and conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…These preliminary findings are uniquely impor-tant given that the wildlife-livestock-human interface is a fertile location for the exchange of disease-causing microorganisms, including pathogens of animal health and zoonotic importance [14][15][16][17][18][19]24,25]. Zoonotic diseases of global importance have previously been shown to be transmitted at this interface, including rabies, Ebola, anthrax, trypanosomiasis and tuberculosis [14][15][16][17][18][19][26][27][28][29]. This complex disease situation is compounded by the presence of AMR [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…These preliminary findings are uniquely impor-tant given that the wildlife-livestock-human interface is a fertile location for the exchange of disease-causing microorganisms, including pathogens of animal health and zoonotic importance [14][15][16][17][18][19]24,25]. Zoonotic diseases of global importance have previously been shown to be transmitted at this interface, including rabies, Ebola, anthrax, trypanosomiasis and tuberculosis [14][15][16][17][18][19][26][27][28][29]. This complex disease situation is compounded by the presence of AMR [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zambia is categorised under the countries where the problem of anthrax in Africa has reached a hyper-endemic state given the incessant and the long-drawn-out outbreak periods that seem unceasing in the recent years (World Anthrax Data Site 2007 ). The disease has had a modifying effect across families, public health institutions and ecotourism in the affected areas of the Western Province as well as other parts of Zambia, such as the Luangwa Valley (Kamboyi 2015 ). Despite the Western Province being the most sparsely populated place in Zambia, with a human population density of less than five people per square kilometre (IUCN 2003 ), outbreaks and occurrence of anthrax in cattle are markedly more noticeable in this area than any other area in Zambia.…”
Section: Introductionmentioning
confidence: 99%
“…The cattle population in the Western Province is estimated to be over 760 000 but is continuously under serious threat not only to anthrax but also to contagious bovine pleuralpneumonia among other diseases (National Livestock Epidemiology and Information Centre 2015 ). The place has the highest incidence and prevalence of anthrax in Zambia, with cultural practices and beliefs of the local people being identified as significant risk factors coupled with the ecological set-up (Kamboyi 2015 ; Munang’andu et al 2012 ; Siamudaala et al 2006 ). The disease endemicity is a result of appropriate mix of environmental and epidemiological factors.…”
Section: Introductionmentioning
confidence: 99%
“…The latter might feature grazing over several infectious sites or, otherwise, on one former carcass site carrying the different genotypes from the body fluids of the dead animal [20,40]. The test was sequentially attempted to detect B. anthracis through blood agar culture and Gram staining, which was then affirmed by multiplex PCR [17]. Tests were examined using MLVA and SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis showed that the collective prevalence estimate from 1992 to 2020 was 24%. It is observed from the pooled publications (Figure -2) that the global prevalence of anthrax varies between 2% and 44%, and atmospheric temperature, soil characteristics, rainfall, and river floods contribute to the spread of the pathogen and have a profound effect on the disease [17,42,43]. However, the effects of precipitation or vegetative green-up on bacterial physiology Available at www.veterinaryworld.org/Vol.14/May-2021/26.pdf or miniature nature to drive anthrax outbreaks are unknown [44].…”
Section: Discussionmentioning
confidence: 99%